Coiled Tubing Circular Efficiency: A Systematic Literature Review on Failure Mechanisms, Inspection Methods, and Reuse Potential - Warno; Suharjito (Testing Center for Oil and Gas LEMIGAS, 2025)
Coiled tubing (CT) has become a critical technology in oil and gas operations, yet its service life is constrained by fatigue, corrosion, and erosion. In marginal fields, the high capital cost of new CT strings for permanent installations such as gas lift creates significant economic challenges. Reusing existing CT assets presents a cost-efficient and sustainable alternative. This study conducts a systematic literature review of 33 Scopus-indexed journal and conference publications to examine CT failure mechanisms, integrity inspection methods, and the economic potential of reuse in marginal fields. The reviewed data were classified by failure mode, inspection technique, application, and economic perspective. The findings reveal that low-cycle fatigue is the most extensively studied failure mode, with wall thickness reduction identified as a key indicator of structural degradation. Current integrity assessments rely heavily on predictive modelling and non-destructive evaluation (NDE) methods, particularly magnetic flux leakage (MFL) and eddy current testing (ECT). Nevertheless, the absence of reliable, field-practical wall thickness measurement remains a critical gap, for which ultrasonic testing (UT) emerges as a promising solution. Case studies further demonstrate the technical feasibility and cost-effectiveness of CT reuse. This review underscores the importance of transitioning from a linear “use-and-scrap” paradigm toward a circular “use-inspect-reuse” framework, with UT serving as a pivotal enabler. This approach enhances economic viability and advances alignment with the United Nations Sustainable Development Goals.